Finite Element Method in Modeling of Ship Structures. Part I – Theoretical Background - Doan, D.; Szeleziński, A.; Murawski, L.; Muc, A. (Scientific Journal of Gdynia Maritime University, 2017)
The paper presents basic knowledge about Finite Element Method including the modeling method of ship structures. Numerical modeling methods were also shortly described. A ship hull and an upper works is typical thin-wallded structure. Modeling method of plates (typical 2-D elements) with stiffeners (1-D elements) is presented in details. In the part II of the article the practical example of Ro-Ro ship's deck analyses was performed with using Patran-Nastran software (MSC Software). The most common and dangerous risks and errors occurring in the process of ship structure modeling were discussed.